3D printing and spine surgery. (28th May 2020) - Senkoylu, Alpaslan; Daldal, Ismail; Cetinkaya, Mehmet
Rapid prototyping (RP), also known as three-dimensional printing (3DP), allows the rapid conversion of anatomical images into physical components by the use of special printers. This novel technology has also become a promising innovation for spine surgery. As a result of the developments in 3DP technology, production speeds have increased, and costs have decreased. This technological development can be used extensively in different parts of spine surgery such as preoperative planning, surgical simulations, patient–clinician communication, education, intraoperative guidance, and even implantable devices. However, similar to other emerging technologies, the usage of RP in spine surgery has various drawbacks that are needed to be addressed through further studies.